Cyclodextrin-grafted polymers functionalized with phosphanes: a new tool for aqueous organometallic catalysis - Potier, Jonathan; Menuel, Stéphane; Mathiron, David; Bonnet, Véronique; Hapiot, Frédéric; Monflier, Eric (Beilstein Journal of Organic Chemistry, 2014)
New cyclodextrin (CD)-grafted polymers functionalized with water-soluble phosphanes were synthesized in three steps starting from polyNAS. Once characterized by NMR spectroscopy and size-exclusion chromatography, they were used as additives in Rh-catalyzed hydroformylation of 1-hexadecene. The combined supramolecular and coordinating properties of these polymers allowed increasing the catalytic activity of the reaction without affecting the selectivities.
Keywords: biphasic catalysis; cyclodextrin; hydroformylation; phosphane; polymer